2014
DOI: 10.1175/mwr-d-13-00007.1
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Goshen County, Wyoming, Tornadic Supercell of 5 June 2009 Using EnKF Assimilation of Mobile Mesonet and Radar Observations Collected during VORTEX2. Part I: Experiment Design and Verification of the EnKF Analyses

Abstract: High-resolution Doppler radar velocities and in situ surface observations collected in a tornadic supercell on 5 June 2009 during the second Verification of the Origins of Rotation in Tornadoes Experiment (VORTEX2) are assimilated into a simulated convective storm using an ensemble Kalman filter (EnKF). A series of EnKF experiments using a 1-km horizontal model grid spacing demonstrates the sensitivity of the cold pool and kinematic structure of the storm to the assimilation of these observations and to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…However, the eastwarddirected difference in the track of the storm in 1kmMY1A relative to the other experiments is consistent with this mechanism of propagation. Similar structures have also been noted and described in several recent observational studies of supercells (Wurman et al 2007;Marquis et al 2008;Wurman et al 2010;Kosiba et al 2013;Lee et al 2012;Markowski et al 2012;Marquis et al 2014;Skinner et al 2014). This effect is in addition to the more dominant components of motion associated with advection by the mean wind and the dynamic interactions of the storm updraft and mesocyclone with the ambient shear (Zeitler and Bunkers 2005).…”
Section: Forecasts On the 1-km Grid A Mesocyclone Tracks And Cold Posupporting
confidence: 82%
“…However, the eastwarddirected difference in the track of the storm in 1kmMY1A relative to the other experiments is consistent with this mechanism of propagation. Similar structures have also been noted and described in several recent observational studies of supercells (Wurman et al 2007;Marquis et al 2008;Wurman et al 2010;Kosiba et al 2013;Lee et al 2012;Markowski et al 2012;Marquis et al 2014;Skinner et al 2014). This effect is in addition to the more dominant components of motion associated with advection by the mean wind and the dynamic interactions of the storm updraft and mesocyclone with the ambient shear (Zeitler and Bunkers 2005).…”
Section: Forecasts On the 1-km Grid A Mesocyclone Tracks And Cold Posupporting
confidence: 82%
“…DA algorithms aim to determine the atmospheric state and associated uncertainties by coupling model forecast information with multiple sources of observations and their respective errors. The ensemble Kalman filter (EnKF) is an ensemble DA approach to nonlinear Kalman filtering based on Monte Carlo techniques (Evensen 2003;Guillijns et al 2006), which has been shown to improve the sampling of the IC error space in both meso-and storm-scale ensemble data assimilation systems (Snyder and Zhang 2003;Zhang et al 2004;Dowell et al 2004;Tanamachi et al 2013;Marquis et al 2014;Sippel et al 2013). The EnKF has an unquestionable potential to produce valuable hydrometeorological predictions in Mediterranean Spain, as it combines the skill for an appropriate mesoscale ensemble generation strategy and the transference of information from land regions toward relatively sparsely observed maritime areas (Carri贸 and Homar 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al (2011) indicated that when a radar is far away from a convective system, a positive impact results from assimilating surface observations, as long as the network spacing is less than 20 km. Through assimilating high-resolution Doppler radar radial velocities and in situ surface observations into an EnKF system, Marquis et al (2014) successfully simulated mesocyclone-scale processes in the Goshen County, Wyoming, and the tornadic supercell of 5 June 2009. Yussouf et al (2015) developed a multiscale ensemble-based assimilation and prediction system that can assimilate the radar, surface, and other observations together.…”
Section: Introductionmentioning
confidence: 99%